2014
DOI: 10.1177/1040638714526595
|View full text |Cite
|
Sign up to set email alerts
|

Mammary diffuse fibroadenomatoid hyperplasia in water buffalo (Bubalus bubalis): three cases

Abstract: Abstract. The current report describes 3 rare cases of mammary diffuse fibroadenomatoid hyperplasia in water buffalo (Bubalus bubalis). All of the animals were between 10 and 12 months of age. Grossly, the lesions consisted of severe diffuse swelling with homogeneous large masses in the udder. Surgical removal of the masses was curative. Microscopically, there was severe hyperplasia of the mammary epithelium and numerous well-differentiated and mildly pleomorphic acini and their associated ducts. Moderate prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…Histological findings observed in the current case are similar to those of a mammary fibroadenoma, which is a frequent neoplasm in young rats and women and has also been reported in a heifer (THIBAULT et al, 1997), a young cow (MINA et al, 1994), and a lamb (GULBAHAR et al, 2007). This benign neoplasm generally forms well-delimited nodules; whereas, fibroadenomatoid hyperplasia is characterized by extensive lesions throughout the mammary glands (HANSON et al, 1987, SANT'ANA et al, 2014, as observed in the current case. This case of bovine mammary hyperplasia appears to have good prognosis because there was no recurrence of the mammary lesions for at least 1 year after surgical excision, as observed in the bubaline mammary fibroadenomatoid hyperplasia (SANT'ANA et al, 2014).…”
Section: Pathologysupporting
confidence: 65%
See 4 more Smart Citations
“…Histological findings observed in the current case are similar to those of a mammary fibroadenoma, which is a frequent neoplasm in young rats and women and has also been reported in a heifer (THIBAULT et al, 1997), a young cow (MINA et al, 1994), and a lamb (GULBAHAR et al, 2007). This benign neoplasm generally forms well-delimited nodules; whereas, fibroadenomatoid hyperplasia is characterized by extensive lesions throughout the mammary glands (HANSON et al, 1987, SANT'ANA et al, 2014, as observed in the current case. This case of bovine mammary hyperplasia appears to have good prognosis because there was no recurrence of the mammary lesions for at least 1 year after surgical excision, as observed in the bubaline mammary fibroadenomatoid hyperplasia (SANT'ANA et al, 2014).…”
Section: Pathologysupporting
confidence: 65%
“…In the current case, there were no significant inflammatory lesions associated with the fibroadenomatoid hyperplasia. Similar to the previously reported cases in bubaline females (SANT'ANA et al, 2014), ovarian endocrine influence on the hyperplasia was suspected, given the IHC-labeling results (positive for estrogen and progesterone receptors). In contrast, the feline mammary diffuse fibroepithelial hyperplasia commonly presents with high concentrations of only progesterone receptors (MISDORP, 2002).…”
Section: Pathologysupporting
confidence: 60%
See 3 more Smart Citations